2001
DOI: 10.1007/s002130000669
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan depletion in SSRI-recovered depressed outpatients

Abstract: Rationale: Recently, a number of studies have challenged the finding that acute tryptophan depletion (TD) increases depressive symptoms in medicated, formerly depressed patients. The present study examined the effects of acute nutritional TD on remitted depressed patients currently treated with selective serotonin reuptake inhibitors. In an attempt to clarify conflicting earlier findings, the effects of a number of clinical variables on outcome were also investigated. Methods: Ten patients underwent TD in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 17 publications
4
45
0
Order By: Relevance
“…Moreover, this paradigm produces, within the same time frame as that used in the present study, a resurgence of depressive symptoms in patients previously ameliorated by their antidepressant drug regimen (Delgado et al 1990(Delgado et al , 1999Bremner et al 1997). Most importantly, it can produce a recurrence of depressive symptoms in remitted depressed patients who are no longer taking antidepressant drugs (Smith et al 1997;Moreno et al 2000;Spillmann et al 2001). Consequently, the tryptophan depletion was likely sufficient to attenuate 5-HT transmission in the brain of subjects studied in the present experiments.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, this paradigm produces, within the same time frame as that used in the present study, a resurgence of depressive symptoms in patients previously ameliorated by their antidepressant drug regimen (Delgado et al 1990(Delgado et al , 1999Bremner et al 1997). Most importantly, it can produce a recurrence of depressive symptoms in remitted depressed patients who are no longer taking antidepressant drugs (Smith et al 1997;Moreno et al 2000;Spillmann et al 2001). Consequently, the tryptophan depletion was likely sufficient to attenuate 5-HT transmission in the brain of subjects studied in the present experiments.…”
Section: Discussionmentioning
confidence: 58%
“…There is evidence to indicate that a threshold exists that needs to be exceeded before behavioral effects occur. 379,380 Van der Does 379 reviewed several ATD studies and suggests that the threshold for possible mood effects to occur lies somewhere around a 60% reduction of free plasma TRP. In a study comparing high and low dose ATD in remitted depressed patients, Booij et al 381 reported impaired processing of positive information in all and return of depressive symptoms in some of the participants in the high depletion group (80-90% depletion of plasma TRP levels).…”
Section: Depletion/atdmentioning
confidence: 99%
“…Further research support, however, has since become available. [25][26][27][28] Although each of these studies comprised a relatively small number of patients, the replications are important because of the negative findings mentioned above.…”
Section: Acute Tryptophan Depletionmentioning
confidence: 99%